Validation of solid mechanics models using modern computation techniques of Zernike moments. (1st July 2022) - Vargas-Vargas, Horlando; Sáez-Landete, José; Siegmann, Philip; Camacho-Bello, César
Abstract: Numerical simulation plays an vital role in mechanical engineering, as it allows the prediction of the mechanical behavior of a component, contributing to the improvement of its performance and the optimization of the design. However, before using the numerical model's valuable information, its reliability must be verified in a process called validation. Validation is usually carried out experimentally, measuring the mechanical behavior of a mechanical part or component. If there is a good agreement between the model's prediction and the experimental measurements, the numerical simulation and its predictions are validated. Traditionally, the validation technique consists of identifying the critical areas of the component and checking the agreement between the simulation and the measurements by means of strain gauges located in these areas. More recently, optical techniques for the deformations measurement have gained much interest due to their ability to measure the entire extension of a component captured by the image. This property, called full-field measurement, allows the validation of the whole numerically simulated sample, improving the reliability and precision of the validation. In this procedure, the comparison between the simulated and experimental data requires an image compression process, typically using descriptors based on Zernike moments or any polynomial decomposition. This article presents an improved validation process based on the efficient and accurate calculation of Zernike moments. Concerning the currently used procedures, this new procedure makes it possible to significantly increase the order of image decomposition, the size (i.e., the resolution) of the analyzed region of interest (ROI), and reduce the processing time. All this results in an improvement in validation reliability and the possibility of validating strains/displacements with arbitrary shapes, even with discontinuities. Highlights: Improved validation procedure of simulated and experimental full-field data. Improved validation procedure through accurate computation of Zernike moments. High order decomposition and reduced computation time in full-field data validation. Accurate polynomial decomposition of discontinuities in displacement maps.